The contribution of self-concept on adolescents’ mental health during the Covid-19 pandemic in Indonesia - Suryaratri, Ratna Dyah; Zakiah, Ernita; Oktoriva, Amelia Syuhada (International Journal of Research in Counseling and Education, 2021)
The Covid-19 pandemic and the issue of mental health among adolescents is one of the important issues that need to be responded. However, there have been few studies amongst Indonesian adolescents that have been conducted. Therefore, the purpose of this study was to analyze the contribution of self-concept toward the mental health of Indonesian Adolescents during the Covid-19 pandemic. The method used in this study is the quantitative research method and regression analysis was conducted to test the hypothesis. The population of this study is Indonesian adolescents and the sampling technic used in this study is convenience sampling. The participants included109 adolescents, specifically 20 boys, and 89 girls, with a mean of19.9. They were asked to complete a set of self-report questionnaires, including Personal Self-Concept (PSC) and Mental Health Inventory (MHI-18). The results showed a positive and significant influence of self-concept on adolescent mental health with a variance of41.5%. The finding of this study highlights the importance of promoting a positive self-concept in supporting adolescent mental health, especially during pandemics. The result of this study also alerts educators in universities and government agents the need to prevent and respond adequately to the negative effect of the pandemic on adolescent mental health.